2020
DOI: 10.3390/su12229704
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Producing Compost from Source-Separated Municipal Organic Waste (A Case Study in Shiraz, Iran)

Abstract: Developing countries face serious environmental, social and economic challenges in managing different types of organic waste. Proper treatment strategies should be adopted by solid waste management systems in order to address these concerns. Among all of the treatment options for organic waste, composting is the most approved method as an effective strategy to divert solid waste from landfills. This experimental research aimed to examine the potential of producing compost from source-separated municipal organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 47 publications
3
15
0
3
Order By: Relevance
“…The temperature was decreased to reach the ambient temperature (28-31 °C) at end of the composting, which is in full agreement with literature [11,18]. The composting process is based on the self-heating of waste and therefore, it is characterized as bio-thermal process.…”
Section: Temperaturesupporting
confidence: 89%
See 2 more Smart Citations
“…The temperature was decreased to reach the ambient temperature (28-31 °C) at end of the composting, which is in full agreement with literature [11,18]. The composting process is based on the self-heating of waste and therefore, it is characterized as bio-thermal process.…”
Section: Temperaturesupporting
confidence: 89%
“…These results are attributed to the consumption of the carbon and nitrogen during the biodegradation of organic substances with microorganisms in composting process. For EC values, the obtained results are 5.5 mS/cm for rotary unit and 6.04 mS/cm for stationary unit, which is in the range of the recommended standard EC values (0-10 mS/cm) [11] where EC value ranges from 2-5 mS/cm and it is considered an average salinity and must be mixed with soil with a ratio of 2:5 for all farming applications, while EC values (5-10) mS/cm is considered medium to high salinity and must be mixed with a ratio of 3:10 where soluble salt level (salinity) in the sample is estimated based on the measurements of the electrical conductivity [20]. Low values of NPK can indicate a lack of available minerals, while high values are indicating a large amount of soluble minerals that may inhibit biological activity or cause problems with land applications if large quantities of the materials are used [16,17].…”
Section: C/n Ratiosupporting
confidence: 53%
See 1 more Smart Citation
“…The volume reduction is a result of the organic matter degradation by microbial activity during the composting process has also been pointed out by several investigators [10,32]. Additionally, previous studies investigating the change of physical properties of organic wastes during the composting phase have demonstrated that high levels of biodegradable organic matter increased the capacity of the microorganisms to oxidise the material, and consequently reduced the volume [17,33].…”
Section: Volume Reductionmentioning
confidence: 69%
“…Although several studies have addressed the optimization of composting of various organic wastes [7,10,11,[14][15][16][17], information on composting of biodegradable domestic solid wastes using effective microorganism inoculants as an accelerator to speed up the composting process and increased nutrients in the compost has not been well documented. Therefore, it is essential to study the effect of microbial inoculant on the composting process.…”
Section: Introductionmentioning
confidence: 99%